Silicon carbide- from synthesis to application: A review - Mohd Sohor, M.A.H. (EDP Sciences, 2017)
This paper provides a review of the synthesis techniques that are used to produce nanostructured silicon carbide. The synthesis methods, consisting of carbothermal reduction, chemical vapor deposition, laser ablation, sol-gel and microwave heating are described. The silicon carbide properties and application are also explained. The paper then discusses the limitations of previous studies which involved complicated equipment and processes, that limit their further application and act as a barrier to further research and development in many fields. © The authors, published by EDP Sciences, 2017.